Pengaruh Penambahan Enkapsulasi Ekstrak Daun Afrika (Vernonia amygdalina)dalam Air Minum terhadap Persentase Karkas, Lemak Abdomen, dan Organ Limfoid Broiler: The Effect of Addition African Leaf Extract (Vernonia amygdalina) Encapsulation via Drinking on The Percentage of Carcass, Abdomen Fat, and Lymphoid Organs of Broilers - Fadilla, Muthia; Fati, Nelzi; Irda, Irzal (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2025)
Background: Common farmers use feed additives such as acidifiers, phytobiotics, and probiotics to replace antibiotics. African leaves are   traditional plants that can be used as a  commercial substitute for feed additives. Purpose: This study aims to determine the impact of adding African leaf encapsulation and the best dose of African leaves in drinking water on the percentage of abdomen fat, carcass, and lymphoid organs of broilers. Methods. The study was conducted experimentally using RAL (Completely Randomized Design) which included 5 replications and 4 treatments, all treatment units consisted of 5 chicks. The treatments was the addition of African leaf extract  encapsulation in drinking water, namely without encapsulation of African leaf extract (EEDA)(A), 0.5% EEDA (B), 1% EEDA (C), and 1.5% EEDA (D). The research parameters included carcass percentage, abdomen fat percentage, thymus, Bursa fabricius, and  broiler thyroid. Results: The resut of the study showed that the addition of african leaf extract encapsulation in drinking water had no significant effect (P>0,05) on the percentage of carcass, abdomen fat, and lymphoid organs. Conclusion: Based on the research result, it can be concluded that the addition of african leaf extract encapsulation in drinking water as a feed additive does not effecet (P>0,05) the percentage of carcass, abdomen fat, and lymphoid organs of broilers. The addition of EEDA in drinking water can be reduced to 1,5% on the percentage of carcass, abdomen fat, and lymphoid organs of broilers.